Different cleat models do not influence side hop test performance of soccer players with and without chronic ankle instability - Silva, D. C. F.; Santos, R.; Vilas-Boas, J. P.; Macedo, R.; Mesquita Montes, A.; Sousa, A. S. P. (Journal of Human Kinetics, 2019)
The lateral ankle sprain is one of the most common sport injury, representing 10-30% of all musculoskeletal disorders. The lateral ankle sprain is induced by sport gestures involving changes of direction and landing manoeuvres and constitutes a risk factor for the occurrence of chronic ankle instability. Although cleat models and performance have been already explored, no study has evaluated this relationship in athletes with chronic ankle instability. Therefore, the purpose of the study was to analyse the influence of different soccer cleat models on Side Hop Test performance of athletes with and without chronic ankle instability. Thirty-nine athletes were divided into two groups, a chronic ankle instability group (n = 20) and a healthy group (n = 19). Each participant performed the Side Hop Test, executing 10 consecutive jumps on dry artificial grass with 4 cleat models. The Qualisys System and two force platforms were used to analyse the test runtime, the distance travelled and the mean velocity. No statistically significant interaction was observed between the group and the cleat model for all variables evaluated. In addition, no differences were observed between models or groups. In this specific test, performance does not seem to be influenced by different cleat models on dry artificial grass in athletes with and without chronic ankle instability.